MEANS OF SOFTENING OF CATEGORICAL EXPRESSIONS AND MITIGATING STRATEGIES IN BUSINESS COMMUNICATION (based on Italian and Spanish business correspondence) - Гринько, Л. В. (Zapiski z romano-germansʹkoï fìlologìï, 2018)
This article examines the conditions for the implementation of the mixing strategy in Spanish and Italian business writing communications. An attempt is being made to determine whether mitigation is a strategy or tactic in business communication. In this regard, these two concepts borrowed from many sciences, including linguistic, from military terminology are considered. In this paper, the mitigation is considered as a communicative strategy involving the use of a number of tactical techniques for the implementation of which language means are involved. Communicative category of mitigation considered as an element of communicative consciousness, which regulates the communicative behavior of communication participants. The linguistic pragmatics category of categorical utterance and linguistic means of its softening that realize communicative mitigation are investigated. The communicative category of mitigation (from the Latin verb 'mitigare' - to mitigate) is associated with a decrease in the illocutionary force of influence on the addressee in special communicative situations, namely, in potentially conflicting situations that often arise in business communication. Strategy mitigation, as well as tactical techniques of its implementation, is also the subject of research in the sciences related to management. They are of considerable interest to politicians, journalists, etc. On the one hand, the mixing strategies are considered in connection with the categories of cooperation, courtesy, trust, tolerance, non-domination and equality, on the other, conflict and rivalry, domination and inequality. The article states that, being associated with courtesy and mitigation of categoricality, tying however not their synonym is. Mitigation is a strategy, a means of expressing courtesy and softening categorical manner of statement - just some of the number of tools, techniques and moves tactically used in this communicative strategy. The linguistic characteristics and pragmatic tools of communicative language interaction in the process of updating their communicative intentions are studied. The linguistic behavior of participants in business correspondence is structured through the implementation of a communicative strategy, which is defined as a complex of pragmatically oriented speech actions aimed at achieving a communicative goal with the use of language tactics that contribute to the implementation of this strategy. In the course of the study, we draw conclusions about the role of pragmalinguistic tools for realizing the communicative strategy of mitigation in achieving success in business communication and the perlocutive effect.